2022
DOI: 10.1007/s00421-022-05041-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions for vascular health and the role of the endothelium

Abstract: The most common non-pharmacological intervention for both peripheral and cerebral vascular health is regular physical activity (e.g., exercise training), which improves function across a range of exercise intensities and modalities. Numerous non-exercising approaches have also been suggested to improved vascular function, including repeated ischemic preconditioning (IPC); heat therapy such as hot water bathing and sauna; and pneumatic compression. Chronic adaptive responses have been observed across a number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 178 publications
0
4
0
Order By: Relevance
“…When human skin is stimulated by rolling manipulation, the effective vasodilator SP in the skin is released from the nerve endings and activates nitric oxide synthase (NOS) in neighboring endothelial cells through the action of IκB kinase. NOS in turn synthesizes nitric oxide (NO), which leads to the expansion of dermal microvascular endothelial cells (DMECs), increases blood flow velocity and improves blood circulation 34 , 35 ) .…”
Section: Discussionmentioning
confidence: 99%
“…When human skin is stimulated by rolling manipulation, the effective vasodilator SP in the skin is released from the nerve endings and activates nitric oxide synthase (NOS) in neighboring endothelial cells through the action of IκB kinase. NOS in turn synthesizes nitric oxide (NO), which leads to the expansion of dermal microvascular endothelial cells (DMECs), increases blood flow velocity and improves blood circulation 34 , 35 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Generating sufficient NO levels to regulate the resistance of the blood vessels and thus maintain adequate blood flow is essential to the healthy performance of the vasculature. It has been reported that exercise training can enhance endothelium-dependent vasodilation in animal and human studies [44][45][46][47]. In general, regular exercise not only increases the production and release of the NO induced by shear stress, but also reduces NO inactivation by upregulating the antioxidant defense mechanism, ultimately leading to an increase in NO bioavailability [48].…”
Section: Plos Onementioning
confidence: 99%
“…Non-pharmacological interventions can significantly alter the blood flow, consequently inducing positive variations in the endothelium. 19 Weight loss decreases venous pressure, and regular exercise increases the tone of the calf muscles to support the vein wall. Exercise also ensures energy expenditure and promotes weight loss.…”
Section: Managementmentioning
confidence: 99%